2004
DOI: 10.1002/jemt.20000
|View full text |Cite
|
Sign up to set email alerts
|

An electron microscopic and biochemical study of the effects of glucagon on glycogen autophagy in the liver and heart of newborn rats

Abstract: The effects of glucagon on the ultrastructural appearance and acid glucosidase activities in the liver and heart of newborn rats were studied. Liver or heart glycogen-hydrolyzing activity of acid glucosidase increased 3 hours after birth and gradually decreased from 3 to 9 hours. Maltose-hydrolyzing activity of acid glucosidase also rose 3 hours after birth, maintained a plateau between 3 and 6 hours, and fell at 9 hours. The administration of glucagon increased autophagic activity in the hepatocytes at the ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…Thus, the hydrolytic degradation assists the phosphorolytic degradation of glycogen in producing glucose (Rosenfeld, 1964;Pfeifer, 1970;Thys, 1970;Shelburne et al, 1973;Glaumann et al, 1985). cAMP and cAMP-elevating agents such as glucagon promote the sequestrational step of hepatocytic autophagy and increase the lysosomal glycogen-hydrolyzing (but not the maltose-hydrolyzing) activity of acid glucosidase, whereas cAMP-antagonizing agents such as propranolol or insulin had opposite results (Kotoulas, 1981(Kotoulas, , 1984(Kotoulas, , 1986Kotoulas et al, 1991Kotoulas et al, , 2003Kalamidas et al, 1994;Holen, 1996;Kalamidas and Kotoulas, 2000b;Kondomerkos et al, 2004).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Thus, the hydrolytic degradation assists the phosphorolytic degradation of glycogen in producing glucose (Rosenfeld, 1964;Pfeifer, 1970;Thys, 1970;Shelburne et al, 1973;Glaumann et al, 1985). cAMP and cAMP-elevating agents such as glucagon promote the sequestrational step of hepatocytic autophagy and increase the lysosomal glycogen-hydrolyzing (but not the maltose-hydrolyzing) activity of acid glucosidase, whereas cAMP-antagonizing agents such as propranolol or insulin had opposite results (Kotoulas, 1981(Kotoulas, , 1984(Kotoulas, , 1986Kotoulas et al, 1991Kotoulas et al, , 2003Kalamidas et al, 1994;Holen, 1996;Kalamidas and Kotoulas, 2000b;Kondomerkos et al, 2004).…”
Section: Discussionmentioning
confidence: 94%
“…cAMP or cAMP-dependent protein kinase, which induce autophagy, have been found to exert a stimulatory effect on PP2A activity, counteracting the inhibitory effect of insulin Ragolia, 1996, 1999;Usui et al, 1998;Cutler et al, 1999;Hartley and Cooper, 2002;Feschenko et al, 2002;Moon and Lerner, 2003). Preliminary experiments showed that cAMP-elevating glucagon, which induces glycogen autophagy (Kondomerkos et al, 2004), caused an increase in the 10 nM okadaic acid-inhibitable casein phosphatase (including PP2A or PP2A-like) activity (control: 85 Ϯ 37 nmol P i liberated/ hr/mg protein; glucagon: 523 Ϯ 203 nmol P i liberated/ hr/mg protein; P Ͻ 0.05, n ϭ 4). This observation supports the view expressed by others that the cAMP and mTOR pathways appear to play parallel roles and converge to the regulation of autophagy and other processes Peterson et al, 1999;Feschenko et al, 2002;Xia et al, 2003).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In the neonatal heart, elevated acid α-glucosidase activity and visualization of glycogen in autophagic vacuoles by electron microscopy is observed during the postnatal period of nutrient deprivation. 50, 51 More detailed dissection of the cardiomyocyte regulatory pathways of insulin signaling, glucose response and glycophagy induction is required.…”
Section: Cargo-selective Autophagy: Macro-autophagy Subtypesmentioning
confidence: 99%